Leaning Against the Wind and the Timing of Monetary Policy - Agur, Itai (IMF Working Papers; Working Paper, 2013)
If monetary policy is to aim also at financial stability, how would it change? To analyze this question, this paper develops a general-form framework. Financial stability objectives are shown to make monetary policy more aggressive: in reaction to negative shocks, cuts are deeper but shorter-lived than otherwise. By keeping cuts brief, monetary policy tightens as soon as bank risk appetite heats up. Within this shorter time span, cuts must then be deeper than otherwise to also achieve standard objectives. Finally, we analyze how robust this result is to the presence of a bank regulatory tool, and provide a parameterized example.